math

Find
dy/dx and d2y/dx2.
x = et, y = te−t

1. 👍
2. 👎
3. 👁
1. x = e^t
y = te^-t

dy/dx = y'/x'
= (1-t)e^-t/e^t
= (1-t)e^-2t

d^2/dx^2 = (x'y"-x"y')/x'^3
= ((e^t)(t-2)e^-t - (e^t)(1-t)e^-t)/e^3t
= (2t-3)e^-3t

or, do it directly

x = e^t, so
y = lnx/x

y' = (1-lnx)/x^2 = (1-t)e^-2t
y" = (2lnx-3)/x^3 = (2t-3)e^-3t

1. 👍
2. 👎
2. thanks. so how woudl i find For which values of t is the curve concave upward?

1. 👍
2. 👎
3. just as usual. Where is y" positive?

e^-3t is always positive, so all you need is

2t-3 > 0
t > 3/2

e^3/2 = 4.48, and you can see from the graph that it is concave upward for x > 4.48

http://www.wolframalpha.com/input/?i=plot+x+%3D+e^t%2C+y+%3D+te^-t+for+1%3C%3Dt%3C%3D2

1. 👍
2. 👎

Similar Questions

1. Chemistry

How would the dx2−y2 orbital in the n=5 shell compare to the dx2−y2 orbital in the n=3 subshell? True or False 1.The contour of the orbital would extend further out along the x and y axes. 2. The value of ℓ would increase by

2. Computer

1: A thesaurus is best used to ________. A Help find the meaning or a word b help find a word that means the same or a similar definition as another word c help find the spelling of a word d help find the pronunciation of a word

3. Calculus

let d2y/dx2= 6x. Find a solution to the differential equation that is continuous for negative infinity to positive infinity and whose graph passes through the point (0,1) and has a horizontal tangent there.

4. Calc

If dy/dx = x²y², then d²y/dx² = ?

1. calculus

Given y^4 -x^4=16 find and simplify d2y/dx2 using implicit differentiation. I got the first derivative which was x^3/y^3 and no im am stuck on using implicit differentiation for the second derivative part

2. Math Compound Interest

If \$500 is invested at an interest rate of 4.5% per year, find the amount of the investment at the end of 11 years for the following compounding methods. (Round your answers to the nearest cent.) Find a, Anually Find b,

3. math

d2y/dx2+9y=cos2x+sin2x

4. Calculus-Math

Find d2y/dx2 in terms of x and y. x^2y^2-2x=3

1. Is this how you derive the formula for arc length?

For a smal change in x, dx: ds² = dx² + dy² ds = sqrt [(dx² + dy²)] s = INTEGRAL of sqrt [(dx² + dy²)] s = INTEGRAL of sqrt [(dx² + dy² * dx²/dx²)] s = INTEGRAL of sqrt[(1 + dy² * 1/dx²)] dx s = INTEGRAL of sqrt[(1 +